A new species of the genus Menimus Sharp, 1876 (Coleoptera: Tenebrionidae: Diaperinae) from Mêdog, Xizang, China - Bai, Xing-Long; Song, Jian; Ren, Guo-Dong (Zootaxa, 2026)
The Chinese species of the genus Menimus Sharp, 1876 are summarized. Nine species are reported in this study, including a new species, M. (M.) medogensis sp. nov., from Xizang. The new species differs from its congeners most notably by the male parameres being strongly emarginate medially on lateral sides, and its larger body size. Habitus and characters of the new species are illustrated. All Chinese species of the genus are listed and keyed.